Hubungan Sosiodemografi Terhadap Perilaku Masyarakat Dalam Swamedikasi Nyeri Di Kelurahan Sempidi Kabupaten Badung - Ni Made Yunitasari; Suryaningsih, Ni Putu Aryati; Maharianingsih, Ni Made; Sutema, Ida Ayu Manik Partha (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Analgesics are one of the most widely used drugs in self-medication, with 35.2 – 59%. This shows the great potential for insecurity in the use of analgesics in self-medication in the community.Self-medication must be carried out according to the disease experienced, its implementation must meet the criteria for using the right drug as much as possible. A person's behavior plays an important role in the accuracy of treatment to support medication safety of analgesic drugs. Differences in sociodemographic factors between communities are considered to influence people's behavior in self-medication for pain, so it is necessary to study this relationship.The research design used is descriptive quantitative with a cross sectional research design. The number of samples used was 96 respondents with purprosive sampling. Measurements were carried out using a questionnaire with data analysis techniques univariate test and multivariate binary logistic regression.The sociodemographic description of the respondents is mostly unmarried 69.8%, aged between 26-45 years 47.9%, dominated by female respondents 75.0%, the majority as private employees & entrepreneurs 53.1% with a Diploma/Bachelor/Level education history of 75.0% and the majority earn <Rp. .1,500.00 as much as 35.4%. The people of Sempidi Village who had poor self-medication behavior were 54.2% and those who had good self-medication behavior were 45.8%. Last education (OR=11.016), gender (OR=8.394), age (OR=3.822) and occupation (OR=4.32) were found to have a significant relationship to the self-medication behavior of the community in pain self-medication. The people of Sempidi Village who carry out pain self-medication are classified as having less self-medication behavior so they are expected to dig deeper information regarding the proper use of analgesic drugs.